2013
DOI: 10.19030/iber.v12i2.7632
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence Of Verdoorns Law In Mexican Manufacturing

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(2 reference statements)
1
0
0
Order By: Relevance
“…Torres et al (2013) found that their results were consistent with Verdoorn’s law when using the OLS method and data from 1985 to 2004 for Mexico. The results show that the states that showed reduced values for the Verdoorn factor (significant for raised yields) were those that experienced more growth than other states.…”
Section: Theoretical Framework and Literature Reviewsupporting
confidence: 63%
“…Torres et al (2013) found that their results were consistent with Verdoorn’s law when using the OLS method and data from 1985 to 2004 for Mexico. The results show that the states that showed reduced values for the Verdoorn factor (significant for raised yields) were those that experienced more growth than other states.…”
Section: Theoretical Framework and Literature Reviewsupporting
confidence: 63%